ANALISIS PENGARUH MANAJEMEN MODAL KERJA, PERTUMBUHAN PENJUALAN DAN KEBIJAKAN HUTANG TERHADAP PROFITABILITAS PERUSAHAAN - Afriyanti Hasanah (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
This study aims to examine the effect of working capital management, sales growth and leverage on profitability. This study uses secondary data with data collection techniques using the annual financial statements of property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. Through the purposive sampling method, 20 companies have met the criteria of a total population of 61 companies, so that the total observation for 5 years is 100 samples. The testing method in this study uses multiple regression analysis with panel data. The results of this study indicate that working capital management does not have an effect on profitability, sales growth variable has an influence on profitability, and leverage variables show no influence on profitability.